Quality Of Nursing Work Life As A Determining Factor Of Nurses’ Performance: An Empirical Study At Kasih Herlina Hospital, Sorong - Gita Manerlin Kasihita Simatupang; Mohammad Agung Saryatmo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to explore the impact of Quality of Nursing Work Life (QNWL) on the performance of nurses at Kasih Herlina Sorong Hospital, focusing on key dimensions such as working conditions, job satisfaction, work-life balance, and various factors that either support or hinder nurses' ability to perform effectively. The research employs a quantitative approach through observational methods, specifically using a cross-sectional research design, which involves collecting data from a defined population at a specific point in time. The intent is to examine how different elements of QNWL contribute to overall job performance. Based on the results obtained, it is evident that components such as work-home life balance, job design, and external work conditions have a significantly positive effect on nurses’ performance. These factors contribute to a more supportive and conducive work environment, thereby enhancing motivation, reducing burnout, and increasing job efficiency. Consequently, when nurses experience better work-life integration, clearly structured job roles, and favorable external work influences, their performance levels tend to improve. Interestingly, the study also reveals that the internal work environment, which may include interpersonal dynamics, organizational culture, or internal policies, does not have a statistically significant influence on performance outcomes within this context. This finding highlights the need for hospital administrators to focus more on improving external factors and job design elements that directly affect nurses’ daily functions. Ultimately, this research provides valuable insights for hospital management seeking to enhance nursing performance through strategic improvements in work-life quality.